Rare bird documentation form for Peregrine Falcon at De Soto Wildlife Refuge, 1978 - Duda, Dorothy Ruthet al (1978)
Rare bird documentation form for a Peregrine Falcon at De Soto Wildlife Refuge in Harrison County, IA on February 24, 1978. Epson - sheet feed/flatbed